DARI OTAK KE AKHLAK : MODEL PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) BERBASIS NEUROSAINS - Fathonah, Nurul; Fatih, Muhammad Amin (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2026)
Traditionally, Islamic Education (PAI) has tended to emphasize normative-cognitive aspects excessively, while failing to fully utilize the mechanisms of the human brain in the learning process. In fact, integrating neuroscience into education offers significant advantages, including enhanced comprehension, the internalization of values, and more effective character building. This article aims to develop a neuroscience-based PAI learning model that integrates cognitive, affective, and psychomotor processes to foster students' akhlak (moral character). The methodology employed is a literature study, analyzing neuroscience theories, learning theories, and the specific characteristics of Islamic Education. By applying principles of meaningful learning, positive emotional engagement, multisensory stimulation, reflection, and experience-oriented approaches, this study concludes that a neuroscience-based model for PAI is highly viable. The implications of this model include the realization of an Islamic Education process that is more humanistic, contextual, and effective in cultivating noble character in students.